FAKTOR RISIKO KEJADIAN ABORTUS (STUDI DI RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG) - Maghni Amalia; sayono s (Jurnal Kesehatan Masyarakat Indonesia, 2015)
Background: Abortus is one of the pregnancy can cause of maternal mortality, and hemorrhageresulting from infection. Risk factors abortion this is some kinds of age mother is pregnant at the time mother, disease abnormality genetalia mother physical activity trauma and chromosomal translocation. Objective: To determine the risk factors of abortion in Islamic Hospital Sultan Agung Semarang. Methods : Case-control study was conducted in 126 pregnant mothers in islam hospital sultan agungsemarang, which is 63 pregnant mother had abortus inkompletus and abortus kompletus (case) and 63 pregnant mother had threatened abortion (control). The dependent variable is the incident abortus inkompletus and abortus kompletus and the independent variable are the age of the mother during pregnancy, maternal parity, maternal employment, hypertension, and levels of hemoglobin. Results : Mostly (56.3 %) pregnant women aged in a category a high risk (less 20 years or more 35 years), 76,2 % have high risk of parity, 56,3 % of worked, 58,7 % do not have hypertension, and 58,7 % do not have anemia. The results of the analytical analysis showed no significant relationship between age of the mother during pregnancy, maternal parity, maternal employment, hypertension, and hemoglobin concentration on the incidence of abortus inkompletus and abortus kompletus (respectively p 0,031; 0,021; 0,004; 0,007; 0,019). Conclusion: The age of the mother during pregnancy, maternal parity, maternal employment, hypertension, and hemoglobin levels are risk factors of abortus inkompletus and abortus kompletus.